(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
In article is given the concepts of "soft" and "hard" skills and their importance in the development of a professional in a professional field, and notes the general and specific features of the approaches to understanding "softskills" and "hardskills" competencies in research in this area.